ChemInform Abstract: A Facile One Pot Strategy for the Synthesis of Well‐Defined Polyacrylates from Acrylic Acid via RAFT Polymerization. Issue 19 (13th May 2014) - Li, Qianbiao; Wang, Taisheng; Dai, Jingwen; Ma, Chao; Jin, Bangkun; Bai, Ruke
Abstract A new one‐pot procedure to synthesize linear and hyperbranched polyacrylates is reported.